Od "Načertanija" do Slobodana Miloševića / From "The Načertanije" to Slobodan Milošević - Memišević, Hamza (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
A review of a book Death in The Hague: Unfinished trial of Slobodan Milošević by Nevenka Tromp (University press - editions Magistrat, 2019).